Compatibility Studies on Elastomers and Polymers with Ethanol Blended Gasoline. (29th January 2014) - Dhaliwal, J. S.; Negi, M. S.; Kapur, G. S.; Kant, Shashi
Abstract : This paper reports the compatibility studies of 10% ethanol blended gasoline (E10) with four types of elastomer materials, namely, Neoprene rubber, Nitrile rubber, hydrogenated Nitrile butadiene rubber (HNBR), and Polyvinyl chloride/Nitrile butadiene rubber blend (PVC/NBR), and two types of plastic materials, namely, Nylon-66 and Polyoxymethylene (Delrin). These materials have applications in automotives as engine seals, gaskets, fuel system seals and hoses, and so forth. Two types of the ethanol blended gasoline mixtures were used: (a) gasoline containing 5% ethanol (E5), which is commercial form of gasoline available in India, and (b) gasoline containing 10% ethanol (E10). The above materials were immersed in E5 and E10 for 500 hrs at 55°C. A set of eight different properties in E5 and E10 (visual inspection, weight change, volume change, tensile strength, percent elongation, flexural strength, impact strength, and hardness) were measured after completion of 500 hrs and compared with reference specimens (specimens at 55°C without fuel and specimens at ambient conditions). Variation observed in different materials with respect to the above eight properties has been used to draw inference about the compatibility of these elastomeric/polymer materials with E10 fuel vis-à-vis E5 fuels. The data presented in this study is comparative in nature between the results of E10 and E5.